2019
DOI: 10.1080/08998280.2018.1540759
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculous cellulitis in an immunocompetent patient

Abstract: Mycobacterial skin infections are rare, with a wide spectrum of clinical features in immunocompromised individuals. Overall, they represent <2% of all forms of extrapulmonary tuberculosis. Tuberculous cellulitis is considered a skin manifestation of miliary tuberculosis. We present a case of tuberculous cellulitis in an immunocompetent patient. KEYWORDS Biopsy; cellulitis; immunocompetent; Mycobacterium tuberculosis C utaneous tuberculosis is an uncommon chronic mycobacterial skin infection, comprising 1% to 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…To date, there have been 7 clinical reports of tuberculous cellulitis in adult patients, including our case ( Table I ). 1 , 3 , 4 , 5 , 6 , 7 All patients were immunosuppressed. Six received steroid therapy, including 3 patients with collagen vascular disease, 4 , 5 1 with diabetes, 1 1 with chronic hepatitis, 3 and a renal transplant recipient.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…To date, there have been 7 clinical reports of tuberculous cellulitis in adult patients, including our case ( Table I ). 1 , 3 , 4 , 5 , 6 , 7 All patients were immunosuppressed. Six received steroid therapy, including 3 patients with collagen vascular disease, 4 , 5 1 with diabetes, 1 1 with chronic hepatitis, 3 and a renal transplant recipient.…”
Section: Discussionmentioning
confidence: 99%
“…Six received steroid therapy, including 3 patients with collagen vascular disease, 4 , 5 1 with diabetes, 1 1 with chronic hepatitis, 3 and a renal transplant recipient. 7 The extremities were affected in 6 of the 7 patients, 3 , 4 , 5 , 6 , 7 and most developed concomitant bacterial superinfection. Several studies have reported severe tuberculous cellulitis causing erosions and ulcers and myositis, depending on the depth of invasion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations